Analisis Kejadian Tuberkulosis pada Suku Anak Dalam (SAD) di Desa Bukit Suban - Asparian, Asparian; Septiani, Sisca; Sitanggang, Hendra Dhermawan; Syukri, Muhammad; Nasution, Helmi Suryani (Universitas Baiturrahim, 2024)
Tuberculosis is a chronic disease caused by Mycobacterium tuberculosis. Tuberculosis is one of the risky diseases in Suku Anak Dalam (SAD) because it is far from health aspects, lack of nutritional knowledge, smoking habits and their work which requires interaction with the outside community, thus becoming a source of disease transmission. The aim of this research is to determine the factors associated with the incidence of tuberculosis in the Anak Dalam Tribe (SAD) in Bukit Suban Village, Sarolangun Regency. Methods: This type of research is quantitative research using an analytical observational design with a cross sectional approach. The research sample is the community of Children in the Nggrib Group, namely 30 people using a purposive sampling technique. Data collection used a questionnaire and data analysis was carried out using the chi-square statistical test. Results: The research results showed that the proportion of tuberculosis in SAD Bukit Suban Village was 13.3%. The results of bivariate analysis of statistical tests show that there is a relationship between nutritional status (p-value 0.037 <0.05) and smoking habits (p-value 0.026 <0.05) on the incidence of tuberculosis. However, employment (p-value 0.960 > 0.05) has no relationship with the incidence of tuberculosis in SAD in Bukit Suban Village, Sarolangun Regency. Conclusion: Factors such as nutritional status and smoking habits have a relationship with the incidence of tuberculosis, but work has no relationship with the incidence of tuberculosis in the SAD community of Bukit Suban Village